Moonlight-driven biological choruses in Hawaiian coral reefs - Duane, Daniel; Freeman, Simon; Freeman, Lauren (PLOS ONE, 2024)
Sounds from fish and invertebrates in coral reefs can create persistent cacophonies that can be recorded for ecosystem monitoring, including during nighttime hours where visual surveys are typically not feasible. Here we use soundscape measurements in Hawaii to demonstrate that multiple coral reef communities are rapidly responsive to shifts in nighttime ambient light, with sustained changes in biological sound between moonrise and moonset. High frequency pulse train sounds from fish (0.5-1.5 kHz) are found to increase during moonlight hours, while low frequency fish vocalizations (0.1-0.3 kHz) and invertebrate sounds (2-20 kHz) are found to decrease during moonlight hours. These discoveries suggest that the rising and setting of the moon triggers regular shifts in coral reef ecosystem interactions. Future acoustic monitoring of reef health may be improved by comparing soundscapes during moonlight and non-moonlight hours, which may provide early indicators of shifts in the relative abundance of separate reef communities.